Bacterial Abundance and Community Composition in Pond Water From Shrimp Aquaculture Systems With Different Stocking Densities - Alfiansah, Yustian Rovi; Hassenrück, Christiane; Kunzmann, Andreas; Taslihan, Arief; Harder, Jens; Gärdes, Astrid (Frontiers in Microbiology, 2018)
In shrimp aquaculture, farming systems are carefully managed to avoid rearing failure due to stress, disease or mass mortality, and to achieve optimum shrimp production. However, little is known about how shrimp farming systems affect biogeochemical parameters and bacterial communities in rearing water, whether high stocking densities (intensive system) will increase the abundance of pathogenic bacteria. In this study, we characterized bacterial communities in shrimp ponds with different population densities. Water quality, such as physical parameters, inorganic nutrient concentrations and cultivable heterotrophic bacterial abundances, including potential pathogenic Vibrio, were determined in moderate density/semi-intensive (40 post-larvae m-3) and high density/intensive shrimp ponds (90 post-larvae m-3), over the shrimp cultivation time. Free-living and particle-attached bacterial communities were characterized by amplicon sequencing of the 16S rRNA gene. Suspended particulate matter (SPM), salinity, chlorophyll a, pH and dissolved oxygen differed significantly between semi-intensive and intensive systems. These variations contrasted with the equal abundance of cultivable heterotrophic bacteria and inorganic nutrient concentrations. Bacterial communities were dominated by Gammaproteobacteria, Alphaproteobacteria, Flavobacteriia, Bacilli, and Actinobacteria. Halomonas and Psychrobacter were the most dominant genera in the particle-attached fractions, while Salegentibacter, Sulfitobacter, and Halomonas were found in the free-living fractions of both systems. Redundancy analysis indicated that among the observed environmental parameters, salinity was best suited to explain patterns in the composition of both free-living and particle-attached bacterial communities (R²: 15.32% and 12.81%, respectively), although a large fraction remained unexplained. Based on 16S rRNA gene sequences, aggregated particles from intensive ponds loaded a higher proportion of Vibrio than particles from semi-intensive ponds. In individual ponds, sequence proportions of Vibrio and Halomonas displayed an inverse relationship that coincided with changes in pH. Our observations suggest that high pH-values may suppress Vibrio populations and eventually pathogenic Vibrio. Our study showed that high-density shrimp ponds had a higher prevalence of Vibrio, increased amounts of SPM, and higher phytoplankton abundances. To avoid rearing failure, these parameters have to be managed carefully, for example by providing adequate feed, maintaining pH level, and removing organic matter deposits regularly.